2021
DOI: 10.56957/jsr.v4i2.154
|View full text |Cite
|
Sign up to set email alerts
|

Pengarsipan Dokumen Pada Kantor Badan Pertanahan Nasional Dan Agraria Tata Ruang (Bpn/Atr) Kabupaten Bungo

Abstract: Dalam suatu organisasi tentu adanya hubungan dengan pengelolaan data dan informasi untuk mencapai tujuan organisasi tersebut secara sistematik. Tentunya dalam perkantoran juga sangat penting sistem administrasi. Dengan menggunakan metode deskriptif dengan pendekatan kualitatif, teknik penggumpulan data yang digunakan adalah wawancara serta analisis yang digunakan dengan trianggulasi dengan informan sebanyak 7 orang. HasilPenelitian Pengarsipan dokumen pada Kantor Badan Pertanahan Nasional Kabupaten Bungo sudah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Nahak (2019) sheds light on efforts to preserve Indonesian culture in the era of globalization, particularly targeting the younger generation, employing two methods: Culture Experience and Culture Knowledge. Sendjaja elucidates that Culture Experience entails preserving culture through direct engagement with it (Hamiru et al, 2022). For instance, if the culture in question is traditional dance, communities are encouraged to learn and practice the dance, showcasing it at annual events or festivals, thus ensuring the continuity of local culture.…”
mentioning
confidence: 99%
“…Nahak (2019) sheds light on efforts to preserve Indonesian culture in the era of globalization, particularly targeting the younger generation, employing two methods: Culture Experience and Culture Knowledge. Sendjaja elucidates that Culture Experience entails preserving culture through direct engagement with it (Hamiru et al, 2022). For instance, if the culture in question is traditional dance, communities are encouraged to learn and practice the dance, showcasing it at annual events or festivals, thus ensuring the continuity of local culture.…”
mentioning
confidence: 99%
“…Even though religion, especially Islam came and developed in Indonesia because it heeded the acculturation of two cultures, namely the culture of the ancestors (Javanese) who were influenced by Hindu-Buddhism and Islam which could blend without losing the personality of the existing local culture.These various problems are at least the reason for the importance of maintaining the existence of local wisdom in an area, especially in the realm of improving the competence of the village youth community to be more concerned and love their local culture. Of course, research has been found that discusses strategies for preserving a culture or local wisdom such as research byNugraheni (2017),Nahak (2019), andHamiru et al, (2022) which describe…”
mentioning
confidence: 99%